SOCIAL AND ECONOMIC ESSENCE OF CONCEPTS RELATED TO DIGITAL TECHNOLOGIES IN TOURISM DEVELOPMENT - Amridin Hamdamov (Journal of Artificial Intelligence and Digital Economy, 2024)
This article highlights the role and importance of digital technologies in the development of the tourism industry. In addition, useful information is provided about the socio-economic nature of concepts related to digital technologies. Keywords: Tourism, Digital Technology, Virtual, Digital Economy, Tourist Product